Mechanical behavior of Ti6Al4V produced by laser powder bed fusion with engineered open porosity for dental applications. (February 2022) - Vanmunster, Lars; D'Haeyer, Camille; Coucke, Pauline; Braem, Annabel; Van Hooreweder, Brecht
Abstract: Implant failure due to biofilm formation is a substantial problem in the field of dental prosthetics. A solution has been proposed in the form of implants with a built-in drug reservoir, but combining sufficient strength and longevity with controlled release capability has proven difficult. This work investigates the feasibility of using laser powder bed fusion to create Ti6Al4V structures with open pore channels while maintaining their mechanical stability. These interconnected pore channels are generated by increasing the distance between consecutive melt pools, denominated as oversized hatch spacing. The impact of varying hatch spacing, laser power and scan speed on the degree of porosity was examined, with both an increase in hatch spacing and a decrease in energy density leading to higher porosity. The pore channels were found to be fully interconnected at total porosity values of 14% or more. The compressive modulus, yield strength and ultimate compressive strength are shown to be strongly related to the density of the structure. Based on the minimal strength and full interconnectivity requirements, the optimal additive manufacturing building conditions were determined. The fatigue properties of the resulting samples were investigated under uniaxial and under inclined compression–compression testing according to ISO 14801, which indicated an endurance limit of 217 MPa in the heat treated state. The results indicate that the use of an oversized hatch spacing is suitable for engineering open porous networks. Graphical abstract: Highlights: Oversized hatching can be used to create fully interconnected pore networks. There is a clear link between the building parameters and the achieved porosity. Porosity and mechanical properties can be controlled based on empirical relations. Fatigue behavior of porous samples under uniaxial and inclined loads is promising.